Preparation and application of glass all-solid-state battery with high electrochemical performance
By performing heat treatment under air atmosphere and at high temperatures, the ionic conductivity of NASICON glass-ceramic solid electrolyte is improved, and the problem of low ionic conductivity in the prior art is solved, which significantly improves the electrochemical performance and safety performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202510056599.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
The existing NASICON glass-ceramic solid electrolyte has low ion conductivity, which affects the electrochemical performance and safety performance of lithium-ion batteries.
By performing heat treatment under air atmosphere and at high temperatures, the ionic conductivity of NASICON glass-ceramic solid electrolyte is improved, density is increased, porosity is reduced, and lithium dendrites are avoided growing along the pores.
It significantly improves the electrochemical performance and safety performance of energy storage devices, and at the same time, it is simple in production process, pollution-free to the environment, and has excellent development prospects.
Smart Images

Figure CN119874198A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation and energy storage, and specifically relates to the preparation and application of a high electrochemical performance glass all-solid-state battery. Background Art
[0002] In recent years, with the shortage of fossil energy and the sustainable development of green energy, people are in urgent need of a new energy technology to meet the sustainable development of human society. Lithium-ion batteries have attracted people's attention due to their high energy density, wide voltage window, stable cycle performance and other characteristics, and have been widely used in daily life. Lithium-ion batteries usually use organic liquid electrolytes, but the leakage, combustion and explosion of liquid electrolytes reduce the safety performance of lithium-ion batteries and also limit the use of lithium-ion batteries at high energy density.
[0003] NASICON solid electrolyte has a three-dimensional network structure, lithium ions can move quickly and show high ionic conductivity. The NASICON glass ceramic solid electrolyte obtained by heat treatment has no pores, high density and no lithium dendrites growing through pores or cracks to cause battery short circuit. Therefore, NASICON glass ceramic solid electrolyte shows excellent safety performance. However, NASICON glass ceramic solid electrolyte still has low ionic conductivity and needs to be improved.
[0004] Therefore, the art needs to develop a glass all-solid-state battery with high electrochemical performance that can effectively solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation and application of a glass all-solid-state battery with high electrochemical performance. The preparation comprises heat-treating glass under air atmosphere and high temperature, and improving the ionic conductivity of NASICON glass ceramic solid electrolyte through a suitable heat treatment process, increasing density, reducing porosity, and preventing lithium dendrites from growing along the pores; the NASICON glass ceramic solid electrolyte with high ionic conductivity is assembled with a glass electrode containing a variable valence metal ion oxide into a glass all-solid-state battery, which greatly improves the electrochemical performance and safety performance of the energy storage device; in addition, the production process of the present invention is simple, pollution-free to the environment, and has excellent development prospects.
[0006] To achieve the above object, the present invention provides a method for preparing a glass all-solid-state battery with high electrochemical performance, which is characterized by comprising the following steps:
[0007] Step S1, preparing oxide glass;
[0008] Step S11, weighing 10-18.75 mole percentage of lithium carbonate, 0-12.50 mole percentage of tin dioxide, 25.00-37.50 mole percentage of titanium dioxide, 5-10.25 mole percentage of aluminum oxide and 25-37.50 mole percentage of diammonium phosphate in a mortar, mixing them evenly and pouring them into an alumina crucible;
[0009] Step S12, melting in an air atmosphere to form molten glass;
[0010] Step S13, rapidly cooling the molten glass liquid in an air atmosphere to obtain oxide glass;
[0011] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0012] Step S3, assembling into a glass all-solid-state battery with high electrochemical performance.
[0013] Preferably, in step S12, the melting temperature is 1520° C. and the holding time is 30 min.
[0014] Preferably, in step S13, the molten glass is poured into water for rapid cooling without annealing.
[0015] Preferably, step S2 specifically comprises:
[0016] Step S21, grinding the oxide glass into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0017] Step S22, performing high temperature heat treatment on the pressed cylinder at a temperature 100-400° C. higher than the crystallization starting temperature to obtain a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0018] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0019] Preferably, in step S22, the heat treatment time is 2-24 hours in an air atmosphere.
[0020] Preferably, step S3 specifically comprises assembling the polished surface-high ionic conductivity NASICON glass ceramic solid electrolyte and the variable valence metal ion oxide glass electrode into a high electrochemical performance glass all-solid-state battery.
[0021] Preferably, the variable-valence metal ion oxide glass electrode includes an active material, a conductive agent, a binder and a current collector; the active material is the variable-valence metal ion oxide glass, and the composition of the variable-valence metal ion oxide glass is V2O5-P2O5-B2O3; the conductive agent is acetylene black, the binder is polyvinylidene fluoride, and the current collector is metal copper foil.
[0022] Preferably, the mass ratio of the active material, the conductive agent and the binder is 7:2:1.
[0023] Application of a high electrochemical performance glass all-solid-state battery in energy storage devices.
[0024] The present invention adopts the preparation and application of the above-mentioned high electrochemical performance glass all-solid-state battery, and the beneficial effects are as follows:
[0025] (1) The present invention forms oxide glass by pouring a melt produced in an air atmosphere and at a high temperature into water and rapidly cooling the melt, and obtains a NASICON glass ceramic solid electrolyte with high ionic conductivity by subjecting the oxide glass to a suitable heat treatment process in an air atmosphere and at a high temperature; due to the combined effect of the crystal and the residual glass phase in the NASICON glass ceramic solid electrolyte, the rapid transmission of lithium ions is facilitated, the density is increased, and the short circuit of the battery caused by lithium dendrites is reduced;
[0026] (2) The capacity, cycle stability and safety of high electrochemical performance glass all-solid-state batteries are significantly improved after the high ionic conductivity NASICON glass ceramic solid electrolyte and variable valence metal ion oxide glass electrode are assembled;
[0027] (3) The present invention has a simple production process, low cost, no pollution to the environment, broad application prospects, and excellent development prospects.
[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flowchart of a preparation and application example of a high electrochemical performance glass all-solid-state battery according to the present invention;
[0030] Figure 2 The DSC graph of oxide glass prepared for the preparation and application example of a high electrochemical performance glass all-solid-state battery of the present invention;
[0031] Figure 3The present invention is a preparation and application of a glass all-solid-state battery with high electrochemical performance. Example 9 is a cycle diagram of preparing a NASICON glass ceramic solid electrolyte material with high ionic conductivity and a variable valence metal ion oxide glass with a composition of V2O5-P2O5-B2O3 (VPB) as electrodes to assemble a glass all-solid-state battery with high electrochemical performance;
[0032] Figure 4 This is a cycle diagram of the preparation and application of a high electrochemical performance glass all-solid-state battery according to Example 10 of the present invention, in which a NASICON glass ceramic solid electrolyte material with high ionic conductivity and a variable valence metal ion oxide glass composition of Fe2O3-B2O3 (FeB) are prepared as electrodes to assemble into a high electrochemical performance all-solid-state glass battery. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0034] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0035] Embodiment 1
[0036] like Figure 1 As shown, a preparation of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0037] Step S1, preparing oxide glass;
[0038] Step S11, weighing 18.75 mole percentages of lithium carbonate, 37.50 mole percentages of titanium dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate, mixing them evenly in a mortar, and then pouring them into an alumina crucible;
[0039] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0040] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S0.
[0041] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0042] Step S21, grinding LATP-S0 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0043] Step S22: In an air atmosphere, Figure 2In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 900°C for 2h.
[0044] Step S23: Use a grinding and polishing machine to polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity, in preparation for assembling it with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0045] Embodiment 2
[0046] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0047] Step S1, preparing oxide glass;
[0048] Step S11, weighing 18.75 mole percentages of lithium carbonate, 35.00 mole percentages of titanium dioxide, 2.50 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate in a mortar, mixing them evenly, and then pouring them into an alumina crucible;
[0049] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0050] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S1.
[0051] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0052] Step S21, grinding LATP-S1 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0053] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 900°C for 2h.
[0054] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0055] Embodiment 3
[0056] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0057] Step S1, preparing oxide glass;
[0058] Step S11, weighing 18.75 mole percentages of lithium carbonate, 32.50 mole percentages of titanium dioxide, 5.00 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate, mixing them evenly in a mortar, and then pouring them into an alumina crucible;
[0059] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0060] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S2.
[0061] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0062] Step S21, grinding LATP-S2 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0063] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 900°C for 2h.
[0064] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0065] Embodiment 4
[0066] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0067] Step S1, preparing oxide glass;
[0068] Step S11, weighing 18.75 mole percentages of lithium carbonate, 30.00 mole percentages of titanium dioxide, 7.50 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate in a mortar, mixing them evenly, and then pouring them into an alumina crucible;
[0069] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0070] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S3.
[0071] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0072] Step S21, grinding LATP-S3 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0073] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 900°C for 2h.
[0074] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0075] Embodiment 5
[0076] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0077] Step S1, preparing oxide glass;
[0078] Step S11, weighing 18.75 mole percentages of lithium carbonate, 27.50 mole percentages of titanium dioxide, 10.00 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate, mixing them evenly in a mortar, and then pouring them into an alumina crucible;
[0079] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0080] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S4.
[0081] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0082] Step S21, grinding LATP-S4 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0083] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 900°C for 2h.
[0084] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0085] Embodiment 6
[0086] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0087] Step S1, preparing oxide glass;
[0088] Step S11, weighing 18.75 mole percentages of lithium carbonate, 25.00 mole percentages of titanium dioxide, 12.50 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate, mixing them evenly in a mortar, and then pouring them into an alumina crucible;
[0089] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0090] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S5.
[0091] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0092] Step S21, grinding LATP-S5 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0093] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 900°C for 2h.
[0094] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0095] Embodiment 7
[0096] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0097] Step S1, preparing oxide glass;
[0098] Step S11, weighing 18.75 mole percentages of lithium carbonate, 27.50 mole percentages of titanium dioxide, 10.00 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate, mixing them evenly in a mortar, and then pouring them into an alumina crucible;
[0099] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0100] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S4.
[0101] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0102] Step S21, grinding LATP-S4 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0103] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 1000°C for 2h.
[0104] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0105] Embodiment 8
[0106] A preparation method of a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0107] Step S1, preparing oxide glass;
[0108] Step S11, weighing 18.75 mole percentages of lithium carbonate, 27.50 mole percentages of titanium dioxide, 10.00 mole percentages of tin dioxide, 6.25 mole percentages of aluminum oxide and 37.50 mole percentages of diammonium phosphate, mixing them evenly in a mortar, and then pouring them into an alumina crucible;
[0109] Step S12, melting in an air atmosphere at a melting temperature of 1520° C. and a heat preservation time of 30 min to form a molten glass liquid;
[0110] Step S13: Rapidly cool the molten glass in an air atmosphere. This step does not require annealing to obtain oxide glass LATP-S4.
[0111] Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity;
[0112] Step S21, grinding LATP-S4 into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace;
[0113] Step S22: In an air atmosphere, Figure 2 In Example 1, a NASICON glass ceramic solid electrolyte with high ionic conductivity was obtained by heat treatment at 1100°C for 2h.
[0114] Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0115] Embodiment 9
[0116] A method for preparing a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0117] The surface of the NASICON glass ceramic solid electrolyte with high ionic conductivity obtained in Example 7 was polished using a grinding and polishing machine in preparation for being assembled with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0118] Assembled into a high electrochemical performance glass all-solid-state battery: variable valence metal ion oxide glass V2O5-P2O5-B2O3 (VPB) powder, acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1 and 2 ml of N-methylpyrrolidone were placed in a 50 mL ball mill and ball milled at 400 r / min for 4.5 h, and then the slurry was coated on copper foil.
[0119] The resulting product was dried at 110° C. under vacuum for 10 h, cooled naturally, and then cut into electrode sheets with a diameter of 12 mm using a sheet puncher.
[0120] By assembling the battery in the order of positive electrode shell - electrode sheet - high ionic conductivity NASICON glass ceramic solid electrolyte - lithium sheet - nickel mesh - negative electrode shell, and then sealing the battery with a sealing machine, a high electrochemical performance glass all-solid-state battery (Li / LATP-S4 / VPB) can be obtained.
[0121] The high electrochemical performance glass all-solid-state battery (Li / LATP-S4 / VPB) prepared in this example was tested for charge and discharge using the Blue Electric test system:
[0122] At 0.01-3.0V cut-off voltage and 1Ag -1 The high electrochemical performance glass all-solid-state battery (Li / LATP-S4 / VPB) was tested for constant current charge and discharge cycles at current density, such as Figure 3 As shown, the first cycle discharge capacity is 782 mAh g -1 After 100 cycles, the specific capacity is 111 mAh g -1 , with higher capacity.
[0123] Embodiment 10
[0124] A method for preparing a glass all-solid-state battery with high electrochemical performance comprises the following steps:
[0125] The surface of the NASICON glass ceramic solid electrolyte with high ionic conductivity obtained in Example 7 was polished using a grinding and polishing machine in preparation for being assembled with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
[0126] Assembled into a high electrochemical performance glass all-solid-state battery: variable valence metal ion oxide glass Fe2O3-B2O3 (FeB) powder, acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1 and 2 ml of N-methylpyrrolidone were placed in a 50 mL ball mill and ball milled at 400 r / min for 4.5 h, and then the slurry was coated on copper foil.
[0127] The resulting product was dried at 110° C. under vacuum for 10 h, cooled naturally, and then cut into electrode sheets with a diameter of 12 mm using a sheet puncher.
[0128] By assembling the battery in the order of positive electrode shell - electrode sheet - high ionic conductivity NASICON glass ceramic solid electrolyte - lithium sheet - nickel mesh - negative electrode shell, and then sealing the battery with a sealing machine, a high electrochemical performance glass all-solid-state battery (Li / LATP-S4 / FeB) can be obtained.
[0129] The high electrochemical performance glass all-solid-state battery (Li / LATP-S4 / FeB) prepared in this embodiment was subjected to charge and discharge tests using a blue-electric test system.
[0130] At 0.01-3.0V cut-off voltage and 1Ag -1 The high electrochemical performance glass all-solid-state battery (Li / LATP-S4 / FeB) was tested for constant current charge and discharge cycles at current density, such as Figure 4 As shown, the first cycle discharge capacity is 582mAh g -1 After 100 cycles, the specific capacity is 51mA hg -1 , with higher capacity.
[0131] Therefore, the present invention adopts the preparation and application of the above-mentioned high electrochemical performance glass all-solid-state battery. The preparation is to heat-treat the glass under air atmosphere and high temperature, and improve the ionic conductivity of the NASICON glass ceramic solid electrolyte through a suitable heat treatment process, promote grain growth, improve ionic conductivity, increase density, reduce porosity, and avoid lithium dendrites growing along the pores; the high ionic conductivity NASICON glass ceramic solid electrolyte is assembled with a glass electrode containing a variable valence metal ion oxide into a glass all-solid-state battery, which greatly improves the electrochemical performance and safety performance of the energy storage device; in addition, the production process of the present invention is simple, pollution-free to the environment, and has excellent development prospects.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. Preparation of a high electrochemical performance glass all-solid-state battery, characterized in that: The following steps are involved: Step S1, preparing oxide glass; Step S11, weighing 10-18.75 mole percentage of lithium carbonate, 0-12.50 mole percentage of tin dioxide, 25.00-37.50 mole percentage of titanium dioxide, 5-10.25 mole percentage of aluminum oxide and 25-37.50 mole percentage of diammonium phosphate in a mortar, mixing them evenly and pouring them into an alumina crucible; Step S12, melting in an air atmosphere to form molten glass; Step S13, rapidly cooling the molten glass liquid in an air atmosphere to obtain oxide glass; Step S2, preparing a NASICON glass ceramic solid electrolyte with high ionic conductivity; Step S3, assembling into a glass all-solid-state battery with high electrochemical performance.
2. The preparation of a high electrochemical performance glass all-solid-state battery according to claim 1, characterized in that: In step S12, the melting temperature is 1520°C and the holding time is 30 minutes.
3. The preparation of a glass all-solid-state battery with high electrochemical performance according to claim 1, characterized in that: In step S13, the molten glass is poured into water for rapid cooling without annealing.
4. The preparation of a high electrochemical performance glass all-solid-state battery according to claim 1, characterized in that: Step S2 specifically includes: Step S21, grinding the oxide glass into powder, pressing it into a cylinder in a mold and transferring it to a muffle furnace; Step S22, performing high temperature heat treatment on the pressed cylinder at a temperature 100-400° C. higher than the crystallization starting temperature to obtain a NASICON glass ceramic solid electrolyte with high ionic conductivity; Step S23: polish the surface of the obtained NASICON glass ceramic solid electrolyte with high ionic conductivity using a grinding and polishing machine to prepare for assembly with variable valence metal ion oxide glass into a high electrochemical performance glass all-solid-state battery.
5. The preparation of a glass all-solid-state battery with high electrochemical performance according to claim 4, characterized in that: In step S22, the heat treatment time is 2-24 hours in an air atmosphere.
6. The preparation of a glass all-solid-state battery with high electrochemical performance according to claim 1, characterized in that: Step S3 specifically comprises assembling the polished surface-high ionic conductivity NASICON glass ceramic solid electrolyte and the variable valence metal ion oxide glass electrode into a high electrochemical performance glass all-solid-state battery.
7. The preparation of a high electrochemical performance glass all-solid-state battery according to claim 6, characterized in that: The variable valence metal ion oxide glass electrode includes an active material, a conductive agent, a binder and a current collector; the active material is the variable valence metal ion oxide glass, and the composition of the variable valence metal ion oxide glass is V2O5-P2O5-B2O3; the conductive agent is acetylene black, the binder is polyvinylidene fluoride, and the current collector is a metal copper foil.
8. The preparation of a high electrochemical performance glass all-solid-state battery according to claim 7, characterized in that: The mass ratio of active material, conductive agent and binder is 7:2:
1.
9. Application of the high electrochemical performance glass all-solid-state battery as claimed in any one of claims 1 to 8 in energy storage devices.
Citation Information
Patent Citations
GLASS CERAMIC WITH ION-CONDUCTING RESIDUAL VITREOUS PHASE and process FOR PRODUCING SAME
CN110128017A
Solid electrolyte material, preparation method, electrode and lithium ion battery
CN116315050A
Glass-ceramic sulfide electrolyte and preparation method and application thereof
CN116750973A
Novel alkali-rich metal NASICON type solid electrolyte and preparation method and application thereof
CN116979134A
Lithium-ionically conductive glass-ceramics and cell and gas sensor, using the same
JP2000026135A